Pulmonary tuberculosis unmasked by immune reconstitution inflammatory syndrome in a child with HIV—a case report. (29th September 2015) - Harrison, R; Penn, R; Denniston, S; Hackett, S; Clarke, J; Welch, S
Abstract : Introduction: Immune reconstitution inflammatory syndrome (IRIS) is a phenomenon seen in patients with recovering immune systems, such as those being treated for HIV. Such recovery can prompt an inflammatory response to an illness previously thought fully treated, or unmask occult infection. The authors report the case of a 13-year-old boy who developed airway compromise after starting treatment with highly active antiretroviral therapy (HAART). Case: A 13-year-old Zambian boy was referred to the paediatric HIV team having been diagnosed following an episode of pneumonia. He was found to have bronchiectasis on CT scan and had been persistently coughing, losing weight and increasingly lethargic over the previous 7 months. He had worsening exertional dyspnoea. Sputum and bronchioalveolar lavage were positive for Haemophilus influenzae and pneumococcus, negative for Mycobacterium, pneumocystis and fungi. Mantoux testing was negative. HIV viral load was >9 million/ml and CD4 count was 6×10 6 /l. Initial antiretroviral treatment was abacavir, lamivudine, lopinavir/r and prophylactic co-trimoxazole. His viral load fell rapidly and his CD4 count began to rise. His exertional dypsnoea lessened. He was actively playing sports again. By 8 months of HAART, his health was deteriorating. His dyspnoea and cough were worsening, and he was febrile. Sputum samples were negative for bacteria including acid-fast bacilli, but a repeat Mantoux was increased from 0 mm of induration at diagnosis to 20 mm. Chest x-ray showed tracheal deviation with narrowing of the left main bronchus. Urgent bronchoscopy with showed both internal obstruction and external compression of his left main bronchus with granulomas, some caseating. His lopinavir/r was changed to efavirenz to reduce the likelihood of drug interactions. He was then commenced on quadruple treatment for tuberculosis with steroids. Discussion: Emergence of previously occult infection is common in individuals commencing HAART, especially in those with previously very low CD4 counts. Where TB is involved, initial Mantoux testing may be negative, as this test relies on a functioning immune system to produce an inflammatory response. Worsening symptoms of infection in patients being treated for HIV should always be investigated for the possibility of IRIS, even for infections where previous testing has been normal.